Dissecting the Mechanism of Intracellular Mycobacterium smegmatis Growth Inhibition by Platelet Activating Factor C-16 - Riaz, Muhammad Suleman; Kaur, Anuvinder; Shwayat, Suha Nadim; Behboudi, Shahriar; Kishore, Uday; Pathan, Ansar Ahmed (Frontiers in Microbiology, 2020)
Mycobacterium tuberculosis (M.tb) infection results in approximately 1.3 million human deaths each year. M.tb resides primarily inside macrophages, and maintains persistent infection. In response to infection and inflammation, platelet activating factor C-16 (PAF C-16), a phospholipid compound, is released by various cells including neutophils and monocytes. We have recently shown that PAF C-16 can directly inhibit the growth of two representative non-pathogenic mycobacteria, Mycobacterium bovis BCG and Mycobacterium smegmatis (M.smegmatis), by damaging the bacterial cell membrane. Here, we have examined the effect of PAF C-16 on M.smegmatis residing within macrophages, and identified mechanisms involved in their growth inhibitory function. Our results demonstrated that exogenous PAF C-16 inhibited the growth of M.smegmatis inside phagocytic cells of monocytic cell line, THP1; this effect was partially blocked by PAF receptor antagonists, suggesting the involvement of PAF receptor-mediated signalling pathways. Arachidonic acid, a downstream metabolite of PAF C-16 signalling pathway, directly inhibited the growth of M.smegmatis in vitro. Moreover, the inhibition of phospholipase C and phospholipase A2 activities, involved in PAF C-16 signalling pathway, increased survival of intracellular M.smegmatis. Interestingly, we also observed that inhibition of inducible nitric oxide synthase (iNOS) enzyme and antibody-mediated neutralization of TNF-α partially mitigated the intracellular growth inhibitory effect of PAF C-16. Use of a number of PAF C-16 structural analogues, including Lyso-PAF, 2-O-methyl PAF, PAF C-18 and Hexanolamino PAF, revealed that the presence of acetyl group (CH3CO) at sn-2 position of the glycerol backbone of PAF is important for the intracellular growth inhibition activity against M.smegmatis. Taken together, these results suggest that exogenous PAF C-16 treatment inhibits intracellular M.smegmatis growth, at least partially, in a nitric oxide and TNF-α dependent manner.